Institutional pressures and environmental management accounting system adoption: evidence from Malaysian public listed companies - Nirman Noor Afiqi Mat Yusoh; Tuan Zainun Tuan Mat; Azizah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sustainability has emerged as a vital concern in addressing major environmental problems. Many countries suffer from severe environmental issues, mainly affected by industrial business activities that accumulate over time and adversely impact environmental performance. Moreover, environmental problems are worsening as rapidly as their economic growth. Environmental Management Accounting System (EMAS) can enhance financial and business performances by evaluating financial and physical environment-related information. Despite the prominence of the EMAS, the level of EMAS adoption is still weak, especially in developing countries. This research examines the level of EMAS adoption among public listed companies in Malaysia and the institutional pressures influencing EMAS adoption. The institutional theory is the underlying theory, and data are collected via an online questionnaire. A total of 205 usable questionnaires were collected from the public listed companies in Malaysia. Ordinary Least Squares (OLS) regression analysis was conducted for hypothesis testing. Results indicated that EMAS had been moderately adopted among public listed companies in Malaysia. The findings revealed that the adoption level for Physical EMA (PEMA) and Monetary EMA (MEMA) is moderately adopted. The results indicate that most companies have a budget allocation for environmental activities. Specifically, this research found that coercive and mimetic pressures significantly influenced EMAS adoption among public listed companies in Malaysia. The result appears that normative pressure does not contribute significantly to the EMAS adoption among public listed companies in Malaysia. This research is significant to the companies, policymakers, and environmental regulatory bodies in understanding the level of EMAS adoption in Malaysia. The government and professional bodies should play a dynamic role in promoting EMAS adoption by issuing specific guidelines and environmental training. In addition, this research provides valuable contributions to the existing literature by providing useful insights into the institutional pressures influencing EMAS adoption among public listed companies in developing countries.